2009
DOI: 10.4315/0362-028x-72.5.937
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli ATCC 25922 and Escherichia coli O157:H7 in Apple Juice and Apple Cider, Using Pulsed Light Treatment

Abstract: The main objective of this work was to evaluate the effectiveness of pulsed light (PL) treatment for the inactivation of Escherichia coli in liquids with different levels of clarity. Nonpathogenic E. coli ATCC 25922 and pathogenic E. coli O157: H7 were used as challenge organisms. Butterfield's phosphate buffer (BPB), tryptic soy broth (TSB), apple juice, and apple cider were used as substrates. The inoculated liquids were placed in a thin layer (1.3 mm) into glass chambers (23 by 53 by 11 mm) and exposed to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 19 publications
11
82
1
1
Order By: Relevance
“…PL application in fruit juices is very promising as some studies reflect its effectiveness as a decontamination technique. Among them, Sauer and Moraru (2009) studied the inactivation of Escherichia coli in apple juice (pH: 4.0; 11.3 Brix) and reported 2.7 log reductions (12.6 J/cm 2 , 1.3 mm layer liquid thickness) under static conditions. In addition, they observed up to 7.3 log reductions (8.8 J/cm 2 ) when generated turbulence in the liquid substrate during the PL treatment (3000 rpm, orbital shaker).…”
Section: Introductionmentioning
confidence: 99%
“…PL application in fruit juices is very promising as some studies reflect its effectiveness as a decontamination technique. Among them, Sauer and Moraru (2009) studied the inactivation of Escherichia coli in apple juice (pH: 4.0; 11.3 Brix) and reported 2.7 log reductions (12.6 J/cm 2 , 1.3 mm layer liquid thickness) under static conditions. In addition, they observed up to 7.3 log reductions (8.8 J/cm 2 ) when generated turbulence in the liquid substrate during the PL treatment (3000 rpm, orbital shaker).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the ability of PL to inactivate Salmonella spp., Escherichia coli, E. coli O157:H7, Listeria monocytogenes and Listeria innocua in some products (Bialka & Demirci, 2008;Ozer & Demirci, 2006;Palgan et al, 2011;Sauer & Moraru, 2009;Uesugi & Moraru, 2009). The variability of results (2e8 log reductions) is most likely due to the different target microorganisms, the intensity of the treatment, and the properties of the substrates (MacGregor et al, 1998;Paskeviciute, Buchove, & Luksience, 2010;Sharma & Demirci, 2003;Woodling & Moraru, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…coli ATCC 25922, a nonpathogenic surrogate of pathogenic E. coli O157: H7 ( Muirhead et al, 2006b;Salleh-Mack and Roberts, 2007;Sauer and Moraru, 2009 ), was grown in Tryptic Soy Broth (TSB; Becton, Dickinson and Company, Sparks, MD) for 18 h at 37 °C on a shaking table. Two milliliters of this culture was then mixed with 60 ml 1.08% potassium chloride (KCl) solution.…”
Section: Experimental Designmentioning
confidence: 99%